Acute lung injury after exchange transfusion in two newborns with Glucose-6-phosphate dehydrogenase deficiency - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA; GÜLCAN KERSİN, SİNEM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Transfusion-related lung injury (TRALI) is a condition that develops suddenly within the first six hours after a blood transfusion and it is one of the most important causes of blood transfusion-related mortality. There are few data in the literature about TRALI in the neonatal period. We present two newborn patients who developed TRALI after exchange transfusion due to high bilirubin levels. Our first case was a late preterm LGA baby and was on CPAP. The baby was intubated due to sudden deterioration after the exchange transfusion. Our second case was born at term and, an exchange transfusion was performed on the 5th day of life. He developed respiratory distress unexpectedly soon after the exchange transfusion and was intubated. Glucose-6- phosphate dehydrogenase (G6PD) deficiency was detected in both of our cases. We wanted to emphasize that TRALI should be considered in the differential diagnosis of respiratory distress that develops soon after a transfusion in the newborn period and to draw attention to that TRALI may develop more frequently in patients with G6PD deficiency.
Keywords: Glucose-6-phosphate dehydrogenase; Neonate; Transfusion-related lung injury